  ## Encyclopedia > Lambert W function

Article Content

# Lambert's W function

Redirected from Lambert W function

Lambert's W function, named after Johann Heinrich Lambert, also called the Omega function, is the inverse function of f(w) = w ew for complex numbers w. This means that for every complex number z, we have
W(z) eW(z) = z
Since the function f is not injective, the function W is multivalued. If we restrict to real arguments x ≥ -1/e and demand w≥-1, then a single valued function W0(x) is defined, whose graph is shown. We have W0(0) = 0 and W0(-1/e) = -1.
The Lambert W function cannot be expressed in terms of elementary functions. It is useful in combinatorics, for instance in the enumeration of trees. It can be used to solve various equations involving exponentials and also occurs in the solution of time-delayed differential equations, such as y'(t) = a y(t - 1).

By implicit differentiation, one can show that W satisfies the differential equation

z (1 + W) dW/dz   =   W      for z ≠ -1/e.

The Taylor series of W0 around 0 can be found using the Lagrange inversion theorem and is given by

$W_0 (x) = \sum_{n=1}^\infty \frac{(-n)^{n-1}}{n!}\ x^n$

The radius of convergence is 1/e. This can be extended to a holomorphic function defined on all complex numbers except the real interval (-∞, -1/e]; this holomorphic function is also called the prinicipal branch of the Lambert W function.

Many equations involving exponentials can be solved using the W function. The general strategy is to move all instances of the unknown to one side of the equation and make it look like x ex, at which point the W function provides the solution. For instance, to solve the equation 2t = 5t, we divide by 2t to get 1 = 5t e-ln(2)t, then divide by 5 and multiply by -ln(2) to get -ln(2)/5 = -ln(2)t e-ln(2)t. Now application of the W function yields -ln(2)t = W(-ln(2)/5), i.e. t = -W(-ln(2)/5) / ln(2).

The function W(x), and many expressions involving W(x), can be integrated using the substitution w = W(x), i.e. x = w ew:

$\int W(x)\, dx = x \left( W(x) - 1 + \frac{1}{W(x)} \right) + C$

References:

All Wikipedia text is available under the terms of the GNU Free Documentation License

Search Encyclopedia
 Search over one million articles, find something about almost anything!

Featured Article
 1904 ... biscuit[?] producer (+ 1985) April 3 - Sally Rand[?], dancer (+ 1979) April 7 - Ralph Bunche[?], diplomat, winner of the Nobel Peace Prize April 16 - Fifi D'Orsay, ...  